Laboratory and Clinical Manifestation Correlation of Neonatal Sepsis in Abdul Moeloek Hospital - Azizah, Nailul; Ervina, Leni; Berawi, Khairunnisa; Busman, Hendri; Irawan, Bambang; Yolanda, Jennifer Ester (Jurnal Ilmu Medis Indonesia, 2025)
Purpose: The prognosis of neonatal sepsis critically depends on early detection; however, its nonspecific clinical signs and variable laboratory findings often complicate the timely diagnosis. This study aimed to assess the correlation between clinical manifestations and laboratory results in neonatal sepsis cases, focusing on patients at Abdul Moeloek Hospital. Methodology/approach: A cross-sectional approach was used to analyze the medical records of neonates diagnosed with sepsis between January and June 2024. All neonates admitted to the neonatal unit with suspected sepsis during this period were included in the study. Results/findings: The majority of patients were male (65.1%) and 1 week old (58.7%). Hyperthermia (44.4%) was the most common symptom, followed by a normal heart rate (68.3%) and respiratory rate (81%). Most patients had normal hemoglobin (55.6%) and leukocyte levels (71.4%), low platelet counts (50.8%), and negative culture results (74.6%). Statistically significant correlations were found between heart rate (OR=0.4) and respiratory rate (OR=0.3) and laboratory findings (p<0.05), although the strength was weak to moderate. No significant correlation was observed with body temperature (p=0.412). Conclusions: Heart and respiratory rates were significantly associated with sepsis-related laboratory results, whereas body temperature was not. Most affected neonates were male, one week old, and presented with hyperthermia but otherwise normal vital signs and blood cell counts. Limitations: The limited sample size and study duration suggest the need for further research. Contribution: These findings provide insights into improving the early detection and management of neonatal sepsis, particularly in pediatric care settings in Indonesia.